2017
DOI: 10.1002/ece3.3266
|View full text |Cite
|
Sign up to set email alerts
|

A review of the influence of biogeography, riverine linkages, and marine connectivity on fish assemblages in evolving lagoons and lakes of coastal southern Africa

Abstract: The Holocene evolution of eight South African coastal lakes and lagoons is examined and related to changes in fish composition over that period. Historical and current connectivity with riverine and marine environments are the primary determinants of present‐day fish assemblages in these systems. A small and remarkably consistent group of relict estuarine species have persisted in these coastal lakes and lagoons. The loss or reduction of connectivity with the sea has impacted on the diversity of marine fishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In the Southern zone, altitudinal variation over short distances caused by the Cape Fold Mountains, and a drop in surface and water temperature from the ORA basin to coastal drainages on the southern coast are factors partly responsible for the clustering patterns and low species richness observed for basins in this zone. Studies on southern Africa's fish species richness in coastal marine habitats (Turpie et al 2000) and natural freshwater lakes (Whitfield et al 2017), have observed a similar trend (i.e. decreasing species richness from warm tropical towards cool temperate areas of the subregion).…”
Section: Southern Zonementioning
confidence: 74%
See 1 more Smart Citation
“…In the Southern zone, altitudinal variation over short distances caused by the Cape Fold Mountains, and a drop in surface and water temperature from the ORA basin to coastal drainages on the southern coast are factors partly responsible for the clustering patterns and low species richness observed for basins in this zone. Studies on southern Africa's fish species richness in coastal marine habitats (Turpie et al 2000) and natural freshwater lakes (Whitfield et al 2017), have observed a similar trend (i.e. decreasing species richness from warm tropical towards cool temperate areas of the subregion).…”
Section: Southern Zonementioning
confidence: 74%
“…Several studies (e.g. Jubb 1964, Roberts 1975, Skelton 1993, Darwall et al 2009, Ellender et al 2017, Whitfield et al 2017) have reported a high proportion of localized endemics in this zone, predominantly involving members of the family Cyprinidae. In addition to marked changes in climatic conditions from subtropical to temperate (Kottek et al 2006), geomorphological factors such as the Great Escarpment, a highland arc that stretches from the Atlantic coast near Namibia to the east coast near Mozambique, and the Cape Fold, an exhumed belt of folded Paleozoic mountains (Stankiewicz and de Wit 2005a), are important topographic features responsible for allopatric differentiations of species forming the distinct ichthyofauna of this region.…”
Section: Southern Zonementioning
confidence: 95%
“…1B), and is distinctive both topographically and geologically. Shifting sands and dune building during the late Holocene led to a southward migration of the mouth and the near isolation of the valley from the sea, forming a narrow, 2.5 km long estuarine channel (Sinclair et al , 1986; Whitfield et al , 2017). Verlorenvlei (18° 26’ E; 32° 21’ S) is a mesotrophic, shallow lake ~1 m AMSL with a surface area of ~10 km 2 .…”
Section: Physiographic Settingmentioning
confidence: 99%
“…The lake has an average depth of 2.5 m, reaching a maximum of 5 m, with pH ranging between 6.7 and 9.6 (Sinclair et al , 1986). The water is relatively low in salinity, although more saline conditions are experienced in the lower reaches (Sinclair et al , 1986; Whitfield et al , 2017). Water temperature ranges from 15.2 to 20.4 °C and transparency from 17 to 114 cm.…”
Section: Physiographic Settingmentioning
confidence: 99%
“…Because of southern Africa's dry conditions; a deep covering of sand related to its cratonic origins (Haddon and McCarthy, 2005); and the restricted influence of rifting, the southern African interior has less potential for deep lakes than East Africa. Today, most lakes and wetlands are found along the coast of South Africa, where they are often under significant marine influence (Hill, 1975;Whitfield et al, 2017). Nevertheless, the subcontinental interior holds many endorheic basins of various sizes, most of which are perennially dry or hold seasonally filled playas today, but where geomorphological features provide evidence for long-lived standing water in the past.…”
Section: Regional Settingmentioning
confidence: 99%